Development of a new approach for corrosion-fatigue analysis of offshore steel structures. (January 2023) - Ryan, Helen; Mehmanparast, Ali
Abstract: Corrosion-fatigue is known to be the dominant failure mechanism in offshore structures, such as offshore wind turbines, due to the constant exertion of cyclic loads in highly corrosive environments. In the present study, the existing corrosion-fatigue crack growth (CFCG) theories and models have been firstly reviewed and discussed, and subsequently a new approach has been proposed to accurately describe the corrosion-fatigue behaviour under various loading conditions and frequencies. To examine the validity of the proposed approach, fatigue crack growth experiments were conducted on S355G10+M medium strength steel compact tension, C(T), specimens at different load levels and frequencies. The experimental data were initially analysed using the traditional fracture mechanics parameter ΔK which was shown to have limitations at elucidating the effects of frequency on CFCG rates in the range of 0.2–0.5 Hz. Therefore, a new fracture mechanics parameter was developed that allows these effects to be seen and accounted for more clearly. Furthermore, a new CFCG model was developed, using the introduced fracture mechanics parameter, for predicting the crack growth rates in seawater from the short-term test data in air. The proposed model has been found to correlate well with experimental data from corrosion-fatigue experiments on S355G10+M from this study and S355J2+N structural steel data available in the literature. Highlights: New time-dependent fracture mechanics parameters are developed for CFCG analysis. A new model is developed for predicting the CFCG rate from the air test data. Two subgrades of S355 tested at various frequencies used for validation purposes. Good agreements have been found between the modelled and measured CFCG trends. The long-term CFCG behaviour can be predicted using the short-term air test data.